Edukasi Digital Sebagai Upaya Pencegahan Cyberbullying di SD IT An-Nur BPMAA Pekanbaru untuk Mendukung SDGs 4 - Tuah Kalti Takwa; Abdel Aulia Amarfazira; Adinda Laura Fitrian Dinata; Ernisa Sitorus; Fazle Mawla Pasha Pahlefi; Jovita Florencia; Marcel Khairan; Maria Oktaulina Cahyani Naibaho; Maritza Firdhie Kayla; Muhammad Hakiim Sulung; Syifa Anisa Putri; Tifa Syafira Salsabila (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Cyberbullying is one of the challenges in achieving Sustainable Development Goal (SDG) 4, which is quality education that is safe and inclusive. Cyberbullying has a negative impact on students' psychological well-being and academic performance, especially at the elementary school level. This article aims to explain efforts to prevent cyberbullying through digital education activities conducted at SD IT An-Nur BPMAA, Sumahilang Village, Riau Province. The method used is a qualitative approach involving socialization, counseling, and interactive discussions with students. The activities focused on improving digital literacy, understanding internet ethics, and strengthening mutual respect in the online world. The results of the activities showed that more than 90% of students began to understand the dangers of cyberbullying and the steps that can be taken to prevent it, both as perpetrators and victims. These findings emphasize that digital education plays a strategic role in creating a healthier learning environment, thereby supporting the achievement of quality education in line with SDG target 4.